2022
DOI: 10.1186/s13148-022-01258-y
|View full text |Cite
|
Sign up to set email alerts
|

LINC00114 stimulates growth and glycolysis of esophageal cancer cells by recruiting EZH2 to enhance H3K27me3 of DLC1

Abstract: Objective LINC00114 could promote the development of colorectal cancer, but its mechanism has been rarely discussed in esophageal cancer (EC). Herein, we explored the molecular mechanism of LINC00114 via mediating enhancer of zeste homolog 2/deleted in liver cancer 1 (EZH2/DLC1) axis in EC. Methods LINC00114, EZH2 and DLC1 expression in EC tissues and cells were tested. LINC00114, EZH2 and DLC1 expression were altered in EC cells through transfect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 58 publications
0
5
0
Order By: Relevance
“…Significantly downregulated genes in Tks4 KO cells include EHF, RERG, MMP13, MMP14, BMP5, and DLC1 ( Figure 2 C). These genes are involved in epithelial differentiation and proliferation [ 40 ] and tumor development, with low expression connected to poor prognosis [ 41 , 42 , 43 ].…”
Section: Resultsmentioning
confidence: 99%
“…Significantly downregulated genes in Tks4 KO cells include EHF, RERG, MMP13, MMP14, BMP5, and DLC1 ( Figure 2 C). These genes are involved in epithelial differentiation and proliferation [ 40 ] and tumor development, with low expression connected to poor prognosis [ 41 , 42 , 43 ].…”
Section: Resultsmentioning
confidence: 99%
“…We also found that LINC00114 was significantly upregulated in B-ALL compared to T-ALL ( Table 3 ). Additionally, LINC00114 has been shown to play a role in the development of colorectal cancer [88] and esophageal cancer [89]. ENSG00000227706 has been demonstrated to be associated with multiple myeloma [90] and acute myeloid leukemia [91] and overexpressed in leukemia [92,93].…”
Section: Resultsmentioning
confidence: 99%
“…We demonstrated that PRMT1 could deposit ADMA at SHMT2-R315, and this methylation enhanced SHMT2 protein activity. (4) Excessive accumulation of methylation signals of SHMT2 promoted the levels of glycolysis and indicators related to one-carbon metabolism in ESCA cells. In conclusion, our data revealed an alternative mechanism by which PRMT1 mediated aerobic glycolysis in ESCA, which drove esophageal carcinogenesis by methylating SHMT2.…”
Section: Discussionmentioning
confidence: 99%
“…The frequently reported short survival is mainly attributed to the limited bene t of systemic radiotherapy and the increased incidence of margin involvement in surgical specimens [3]. Notably, surgery combined with chemotherapy remains the preferred treatment for this speci c population of patients with advanced ESCA, but more efforts should be devoted to elucidating the speci c mechanisms of disease progression and establishing mechanism-based therapeutic strategies for patients with potential clinical consequences (recurrence or metastasis) [4,5]. Therefore, the study of tumor biomarkers is a promising approach to control disease progression.…”
Section: Introductionmentioning
confidence: 99%